Developing a National Trauma Research Action Plan: Results from the long-term outcomes research gap Delphi survey. Issue 6 (16th December 2022) - Herrera-Escobar, Juan P.; Reidy, Emma; Phuong, Jimmy; Brasel, Karen J.; Cuschieri, Joseph; Fallat, Mary; Potter, Benjamin K.; Price, Michelle A.; Bulger, Eileen M.; Haider, Adil H.; ,; Bonne, Stephanie; et al.
Abstract : Research on long-term trauma outcomes is scant and must be prioritized as a whole. In this consensus-driven Delphi survey, the most prevalent topic areas among high priority research questions are mental health, post-discharge health services, and the geriatric population. Abstract : BACKGROUND: In the National Academies of Sciences, Engineering, and Medicine 2016 report on trauma care, the establishment of a National Trauma Research Action Plan to strengthen and guide future trauma research was recommended. To address this recommendation, the Department of Defense funded the Coalition for National Trauma Research to generate a comprehensive research agenda spanning the continuum of trauma and burn care. We describe the gap analysis and high-priority research questions generated from the National Trauma Research Action Plan panel on long-term outcomes. METHODS: Experts in long-term outcomes were recruited to identify current gaps in long-term trauma outcomes research, generate research questions, and establish the priority for these questions using a consensus-driven, Delphi survey approach from February 2021 to August 2021. Panelists were identified using established Delphi recruitment guidelines to ensure heterogeneity and generalizability including both military and civilian representation. Panelists were encouraged to use a PICO format to generate research questions: Patient/Population, Intervention, Compare/Control, and Outcome model. On subsequent surveys, panelists were asked to prioritize each research question on a 9-point Likert scale, categorized to represent low-, medium-, and high-priority items. Consensus was defined as ≥60% of panelists agreeing on the priority category. RESULTS: Thirty-two subject matter experts generated 482 questions in 17 long-term outcome topic areas. By Round 3 of the Delphi, 359 questions (75%) reached consensus, of which 107 (30%) were determined to be high priority, 252 (70%) medium priority, and 0 (0%) low priority. Substance abuse and pain was the topic area with the highest number of questions. Health services (not including mental health or rehabilitation) (64%), mental health (46%), and geriatric population (43%) were the topic areas with the highest proportion of high-priority questions. CONCLUSION: This Delphi gap analysis of long-term trauma outcomes research identified 107 high-priority research questions that will help guide investigators in future long-term outcomes research. LEVEL OF EVIDENCE: Diagnostic Tests or Criteria; Level IV. Abstract :